2022
DOI: 10.1007/s00066-022-01984-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk management patterns in radiation oncology—results of a national survey within the framework of the Patient Safety in German Radiation Oncology (PaSaGeRO) project

Abstract: Purpose Risk management (RM) is a key component of patient safety in radiation oncology (RO). We investigated current approaches on RM in German RO within the framework of the Patient Safety in German Radiation Oncology (PaSaGeRO) project. Aim was not only to evaluate a status quo of RM purposes but furthermore to discover challenges for sustainable RM that should be addressed in future research and recommendations. Methods An online survey was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
1
0
3
Order By: Relevance
“…A prior comparable assessment dates back to 1998 24,25 . As previously reported for RD assessment, 26 our results underline that the pharmaceutical RD management remains heterogeneous and is in various aspects still driven by personal preference rather than by evidence‐based recommendations. A European‐American study showed that therapeutic skin care decisions often rely on anecdotal reports rather than evidence; 17 similar observations were made among British radiation oncologists, 20 demonstrating a broad variability in products used between different departments.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A prior comparable assessment dates back to 1998 24,25 . As previously reported for RD assessment, 26 our results underline that the pharmaceutical RD management remains heterogeneous and is in various aspects still driven by personal preference rather than by evidence‐based recommendations. A European‐American study showed that therapeutic skin care decisions often rely on anecdotal reports rather than evidence; 17 similar observations were made among British radiation oncologists, 20 demonstrating a broad variability in products used between different departments.…”
Section: Discussionsupporting
confidence: 70%
“…Thematic subdivisions were demographic data, RD diagnostics and surveillance, prevention and treatment of RD. This report focuses solely on the survey's aspects of pharmaceutical prevention and treatment of RD, while the results for surveillance and non‐pharmaceutical prevention have been published previously 26 . For prophylactic and therapeutic options, a comprehensive list of different pre‐defined agents or approaches was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Der vorliegende Bericht konzentriert sich ausschließlich auf die Aspekte der pharmazeutischen Prävention und Behandlung der RD, während die Ergebnisse zur Überwachung und nicht-pharmazeutischen Prävention bereits veröffentlicht wurden. 26 Für die prophylaktischen und therapeutischen Optionen wurde eine umfassende Liste verschiedener vordefinierter Mittel oder Ansätze erstellt. Um einen zusätzlichen Einblick in das gesamte Spektrum der in den einzelnen Einrichtungen angebotenen Therapien zu erhalten, waren Mehrfachnennungen möglich.…”
Section: Methodik Fragebogenunclassified
“…Thematische Unterteilungen waren demographische Daten, Diagnostik und Überwachung, Prävention und Behandlung der RD. Der vorliegende Bericht konzentriert sich ausschließlich auf die Aspekte der pharmazeutischen Prävention und Behandlung der RD, während die Ergebnisse zur Überwachung und nicht‐pharmazeutischen Prävention bereits veröffentlicht wurden 26 . Für die prophylaktischen und therapeutischen Optionen wurde eine umfassende Liste verschiedener vordefinierter Mittel oder Ansätze erstellt.…”
Section: Methodikunclassified
See 1 more Smart Citation